Menanam Kehidupan Bertoleransi: Studi Kasus Festival Budaya SMP Negeri 1 Harau - Hidayat, Muhammad; Juliana M, Tiara; Ayuningsih, Syofia; Grestiana, Fresia; Elvaririn, Elvaririn (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2025)
This study examines the role of cultural festivals as a strategic instrument for internalizing the values of tolerance and diversity within an educational environment. Employing a qualitative case study approach at SMP Negeri 1 Harau, Limapuluh Kota Regency, the research explores how local cultural expressions are integrated into the curriculum through the Project for Strengthening the Profile of Pancasila Students (P5). Data were gathered through participatory observation and in-depth interviews to analyze the transformation of cultural activities from mere ceremonial displays into ingrained character traits. The findings reveal that cultural festivals function as a pedagogical 'contact zone' that effectively facilitates students' negotiation of differences and strengthens social bonding. The integration of traditional arts serves not only as a vehicle for cultural preservation but also as a fundamental mechanism for fostering inclusivity and mutual respect. This study concludes that local wisdom-based education is pivotal to constructing a harmonious educational ecosystem and providing a robust framework for social cohesion in a pluralistic society.